The Necessity of Clusters for Modern Management - Mihaela (Dan) PREJMEREAN (Revista de Management Comparat International)
The term of cluster as economic agglomeration became in time an obsessive concept for politicians, consultancy organizations, business associations and companies, in general. It is seen as an instrument that guarantees the economic success at local and regional level, one of the solutions to sustain cohesion. We know that clusters connect people and organizations, their activities are interdependent and intertwined. Even so, there are voices that criticize clusters and the approach of Michael Porter who launched the term in the early 90’s. Given this we search for answers about what is a cluster and why should the industrial policy focus on it? What determines organizations to gather in a cluster? Is there a typology of clusters? At the end we make some observations about clusters in Romania and their potential influence on the economic development